Двенадцать месяцев: [сказка-пьеса] / С. Маршак - Маршак Самуил Яковлевич (Библиотека начальной школы, 2017)
Экземпляры: ф.22 (20190112) / Инвентарный номер: 59092 / Цена: / Сис.шифр: 84(2Рос=Рус)6-6 / Авт.знак: М 30 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-6